PENGARUH JUMLAH PENDUDUK, TINGKAT PENDIDIKAN DAN TINGKAT KESEMPATAN KERJA TERHADAP KEMISKINAN DI KABUPATEN JOMBANG (Studi Kasus Pada Masyarakat di Kecamatan BandarKedungmulyo): Studi pada Masyarakat di Kecamatan Bandar Kedungmulyo - Eva Titi Sundari; Marseto Marseto (Al-Buhuts, 2023)
This study aims to determine the effect of population, education level and employment opportunity on poverty in Bandarkedungmulyo District, Jombang Regency. The data in this study were obtained through distributing questionnaires and the data obtained was processed using quantitative methods. Questionnaires were distributed via Google form containing 20 statements, where each variable was represented by 5 statements. Determining the population based on regional characteristics, the researchers determined 311 RTs as the population. Whereas in determining the sample of this study there were 62 respondents, the sample came from 20% of the total population (20% x 311 = 62.2). The analysis technique uses research instrument tests, classical assumption tests, multiple linear regression tests and statistical tests. Processing data using excel and SPSS 27. In this study population, education level and employment opportunity simultaneously have a significant positive effect on poverty.